On split metacyclic groups - Liu, He-guo; Yan, Yang (Ukrains’kyi Matematychnyi Zhurnal, 2012)
Using the properties of primitive characters, Gauss sums, and the Ramanujan sum, we study two hybrid mean values of Gauss sums and generalized Bernoulli numbers and give two asymptotic formulas.